The Mission of the Jerusalem Apostles: An Authorial, Historical and Canonical Reconstruction - Hui, Nathan Kin Yan (My University, 2014)
This dissertation argues that the corpus of so-called Catholic Epistles in the New Testament canon, that is James, 1 and 2 Peter, 1, 2, and 3 John, and Jude, should be accurately called the Jerusalem Apostolic Epistles. These epistles were written by the alleged Jerusalem Apostles, namely James, Peter, John and Jude. Instead of looking at these writings separately, it is proposed that the mission of the Jerusalem Apostles can be discovered by an authorial, historical, and canonical reconstruction of their epistles if they are studied as a collection. These four canonical authors represented three locations of origin, James and Jude from Jerusalem to the Diaspora Jews, Peter from Rome to the Diaspora Jews of eastern Asia Minor, and John from Asia Minor to the vicinity. The seven epistles were closely knitted together like a web through various kinds of connections and similarities.
In the process of the canonization of these epistles, we find that the Jerusalem Apostolicity representing the Jewish Christianity played a role in the church in, on the one hand, separating from first-century Judaism, and, on the other, counterbalancing the Gentile Christianity represented by Paulinism. The latter parting of the ways has been in existence from the days of the apostles to even the days of Augustine. The rise of heresies indirectly stimulated the making of creeds and regula fidei.
Papyrological and patristic evidences show that some of these epistles existed and were in circulation as early as the second century. The Jerusalem Apostles and their writings were recognized, mentioned, quoted, and circulated. There were obstacles for some of the writings of the Jerusalem Apostles to be recognized into the canon. However, in view of the final product and the placement of the canon, all these epistles were compiled together following the Book of Acts to form a single unit of the Apostolos. I propose a canon-logical reconstruction of the Jerusalem Apostolic Theology, and a reading of the Catholic Epistles with literary rearrangement within the Apostolos as part of the discussion of the final canonical product.
This dissertation concludes with my attempt of an authorial, historical, and canonical reconstruction of the mission of the Jerusalem Apostles.
Keywords: mission, Jerusalem Apostles, authorial, historical, canonical, reconstruction, corpus, epistles